2021
DOI: 10.7759/cureus.13619
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety and Obsessive-Compulsive Disorder Are Common Among Persons With Multiple Sclerosis at King Abdulaziz Medical City, Riyadh

Abstract: Background Multiple sclerosis (MS) is associated with a physical disability and disturbed psychosocial functioning in young people. Many psychological and psychiatric comorbidities have been reported in MS. Objective To determine the frequency of social anxiety disorder (SAD) and obsessive-compulsive disorder (OCD) among MS patients and their relation to MS severity. Methods A cross-sectional survey was conducted in an adult MS cohort. Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) and Social Phobia Inventory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…These publications demonstrate that the lifetime prevalence of OCD in patients with MS is at least three times higher than it is in the general population (Korostil and Feinstein 2007 ). The frequency of OCS in MS has been reported to be up to 31% and correlates with the severity of MS (Foroughipour et al 2012 ; Khatri et al 2021 ; Uguz et al 2008 ). MS patients in the exacerbation phase displayed significantly higher rates of OCS than patients in the remission phase.…”
Section: Discussionmentioning
confidence: 99%
“…These publications demonstrate that the lifetime prevalence of OCD in patients with MS is at least three times higher than it is in the general population (Korostil and Feinstein 2007 ). The frequency of OCS in MS has been reported to be up to 31% and correlates with the severity of MS (Foroughipour et al 2012 ; Khatri et al 2021 ; Uguz et al 2008 ). MS patients in the exacerbation phase displayed significantly higher rates of OCS than patients in the remission phase.…”
Section: Discussionmentioning
confidence: 99%
“…The main psychiatric comorbidities in MS patients are obsessive–compulsive disorders (OCD), specific phobias, depression, generalized anxiety, and schizophrenic and bipolar disorders [ 1 , 2 ]. The frequency of OCD among MS patients has been reported to be about 12%–16% [ 3 , 4 ] or even 30% in some populations such as in Saudi Arabia [ 5 ]. A recent descriptive study reported the experience of OCD in 15 patients with MS [ 6 ].…”
Section: Introductionmentioning
confidence: 99%